Gangrenous ischemic colitis localized to the cecum: a case report - Kohei Tateno; Yoko Motegi; Hiroomi Ogawa; Kunihiko Suga; Takuhisa Okada; Katsuya Osone; Ryuji Katoh; Yasunari Ubukata; Hideyuki Saito; Keigo Hara; Makoto Sakai; Kyoichi Ogata; et al. (Surgical Case Reports)
Abstract Background Ischemic colitis affects the left colon in elderly individuals and localization on the right side, especially in the cecum, is rare. We report a case of gangrenous ischemic colitis localized in the cecum of a patient undergoing hemodialysis. Case presentation A 73-year-old man had been undergoing hemodialysis for chronic renal failure caused by diabetic nephropathy. He experienced frequent vomiting, diarrhea, and abdominal pain. Contrast-enhanced computed tomography revealed thickening of the cecal wall, poor enhancement, dilation of the cecum, and intrahepatic portal emphysema. No obvious abnormal findings were observed in the appendix. The patient was diagnosed with cecal necrosis and ileocecal resection was performed. Histopathological examination revealed gangrenous ischemic colitis of the cecum. He was discharged 12 days after surgery without postoperative complications. Conclusion It is important to consider the possibility of ischemic colitis of the right colon in the event of renal failure requiring dialysis, to ensure that opportunities for surgical intervention are not missed.